SUSTAINABLE VALUE OF RICE SUPPLY CHAIN: A SYSTEMATIC LITERATURE REVIEW AND RESEARCH AGENDA - Nurul Maghfiroh; Marimin; Tajuddin Bantacut; Elisa Anggraeni (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
The rice supply chain is important to achieve food security. It has various perspectives, challenges or issues that causes a complex problem in supply chain system. The existing problem are related to food availability, inventory level, fragmented distribution, affordability of prices, accessibility, variation of business processes and the environmental impact from production and logistics system. Moreover integration framework in the dimension of sustainability is limited. The objective of this article is to identify current problems to construct the idea of supply chain integration and to build the formulation for improvement the value of rice supply chain. Fifty articles discuss rice supply chain. The remaining discuss on increasing rice productivity, inventory optimization, performance improvement, and traceability. The VOS viewer result showed that sustainability is connected to the supply chain at a distant position which indicates that sustainability has the opportunity to be studied wider range in future research. The gap analysis showed that the production increase is limited to agronomy innovation and didn’t consider sustainable characteristics input. The indirect innovations that use information technology for precision farming also had not been comprehensively collaborated. The production absorption had not been considered in inventory optimization and traceability system had not been developed for supply availability. The improvement activities to fill the gap will transform supply chain performance more efficient, responsive and minimum environmental impacts for the enhancement of the sustainability value of the rice supply chain. Keywords: gap analysis, integration, rice supply chain, sustainability, production and logistics system